Postoperative 30-Day Comparative Complications of Multilevel Anterior Cervical Discectomy and Fusion and Laminoplasty for Cervical Spondylotic Myelopathy: An Evidence in Reaching Consensus - Ryan Wing-Yuk Chan; Yung-Hsiao Chiang; Hsiu-Chen Lin; Chih-Yau Chang; Yi-Syue Tsou (Diagnostics, 2023)
Although a few large-scale studies have investigated multilevel anterior cervical discectomy and fusion (ACDF) and laminoplasty (LAMP) and their related complications for cervical spondylotic myelopathy (CSM), the optimal surgical intervention remains controversial. Therefore, we compared their 30 days of postoperative complications. Through the 2010–2019 ACS NSQIP Participant Use Data Files, we estimated the risk of serious morbidity, reoperation, readmission, mortality, and other postoperative complications. Initially, propensity score matching (PSM) of the preoperative characteristics of both groups was performed for further analysis. Multivariable logistic regression analysis provided OR and 95% CI for comparative complications. After PSM, 621 pairs of cohorts were generated for both groups. Increased frequency of postoperative complications was observed in the LAMP group, especially for surgical wound infection, no matter whether superficial (ACDF/LAMP = 0%/1.13%, p = 0.0154) or deep wound infection (ACDF/LAMP = 0%/0.97%, p = 0.0309). The mean length of total hospital stays (ACDF/LAMP = 2.25/3.11, p < 0.0001) and days from operation to discharge (ACDF/LAMP = 2.12/3.08, p < 0.0001) were longer, while the hospitalization rate for over 30 days (ACDF/LAMP = 4.67%/7.41%, p = 0.0429) and unplanned reoperation (ACDF/LAMP = 6.12%/9.34%, p = 0.0336) were higher in LAMP. Results also indicated congestive heart failure as a risk factor (adjusted OR = 123.402, p = 0.0002). Conclusively, multilevel ACDF may be a safer surgical approach than LAMP for CSM in terms of perioperative morbidities, including surgical wound infection, prolonged hospitalization, and unplanned reoperation. However, these approaches showed no significant differences in systemic complications and perioperative mortality.